ANALYSIS OF COST STRUCTURE, REVENUE, AND PROFITABILITY OF TOFU PRODUCTION BUSINESS (THE CASE IN UKM WAHYU UTAMA, GUNUNG PUTRI, BOGOR REGENCY) - Siti Rochaeni; Rizki Adi Puspita Sari; Desita Prastiwi (Syarif Hidayatullah State Islamic University Jakarta, 2022)
Tofu is one of the popular processed soybean products for the people of Indonesia. UKM Wahyu Utama is one of the medium-scale tofu processing industries in Bogor Regency, with tofu products sold, namely white tofu which consists of small tofu products and large tofu products. Wahyu Utama UKM, which has been operating since 2018, unfortunately, does not have a systematic cost recording, does not know the income that has been obtained, has not calculated its business efficiency, and is also faced with sales of tofu products in 2021 which tend to decline. The objectives of this study are (1) to Analyzing the cost structure of UKM Wahyu Utama in producing tofu; (2) to Analyze the income of the tofu production business in the Wahyu Utama UKM; (3) to Analyze the level of B/C Ratio, Break Even Point (BEP), and Payback Period (PP) in tofu production business in Wahyu Utama UKM; (4) Analyze the profitability of tofu production business in Wahyu Utama UKM. Types of quantitative research with descriptive analysis. The data source uses primary data and secondary data. The data analysis used is a descriptive analysis to determine the general description of the company, business cost structure, and business income analysis to measure receipts, and revenue, followed by business analysis with B/C Ratio, Break Even Point (BEP), and Payback Period (PP), as well as business profitability analysis with Margin of Safety (MOS) and Marginal Income Ratio (MIR). The results showed that (1) The variable costs needed by UKM Wahyu Utama have a higher percentage compared to fixed costs. (2) Tofu product business revenue in UKM Wahyu Utama in 2021 amounted to Rp 1,234,274,167. (3) The B/C Ratio value in small tofu products is 0.19 and in large tofu products, which is 0.15 (4) The profitability obtained from small tofu products is 16.38 percent, and large tofu products are 13.08 percent.